Precise 210Pb determination with high-efficiency gamma spectrometry for dating of marine sedimentary cores. (February 2020) - Pedrosa-García, M.C.; Fontela, M.; Quintana, B.; Pérez, F.; Francés, G.; Marcos, T.
Abstract: In order to establish the chronology of deep-sea sediments from high-resolution 210 Pb-dating, the determination of 210 Pb and 226 Ra activity concentrations needs to be improved. Gamma spectrometry allows determining simultaneously both radionuclides. However, spectrum background is still an issue to obtain high sensitivity. Four deep-sea sediment cores were dated using Mazinger, a gamma spectrometer with high-efficiency and very low-background, and the Constant Rate and Supply model was applied to obtain recent ages. Highlights: 210 Pb-dating for sediment core of deep-water basins by Mazinger γ-spectrometer. Galea is developed specifically to analyse γ-ray spectra from natural radionuclides. Background and peak efficiencies suitable to the measurement are obtained. The results show a coherence of 210 Pb-dating for sediments cores of deep-water basin.